2015
DOI: 10.3791/52032
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Induced Pluripotent Stem Cells from Muscular Dystrophy Patients: Efficient Integration-free Reprogramming of Urine Derived Cells

Abstract: Dystrophic cardiomyopathy is a poorly understood consequence of muscular dystrophy. Generating induced Pluripotent Stem Cells (iPSCs) from patients with muscular dystrophy is an invaluable cellular source for in vitro disease model systems and can be used for drug screening studies. Patient-derived urine cells have been used in successful reprogramming into induced pluripotent stem cells in order to model dystrophic cardiomyopathy1. Addressing the safety concerns of integrating vector systems, we present a pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 12 publications
0
32
0
Order By: Relevance
“…1a ). Urine was isolated from multiple healthy individuals ( n > 8), and urine cells were isolated and cultured as described [ 22 , 24 ]. Bright-field images from two typical urine cultures demonstrated characteristic urine cell morphology and growth (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1a ). Urine was isolated from multiple healthy individuals ( n > 8), and urine cells were isolated and cultured as described [ 22 , 24 ]. Bright-field images from two typical urine cultures demonstrated characteristic urine cell morphology and growth (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Urine-derived cells (UDCs) are thought to be of a mixed population that originates from either the renal epithelium or the uroepithelium [ 18 , 21 ]. Interestingly, a subset of UDCs has been observed to carry mesenchymal stem cell markers as well as low endogenous expression of Oct3/4, a pluripotency marker [ 4 , 20 , 22 ]. As such, UDCs demonstrate propensity for differentiation into several lineages, one of which is muscle-like [ 20 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…To avoid the side effects, non-integrating protocols using episomal vectors, Cre-lox system, piggybac vectors, minicircles, recombinant proteins, messenger RNAs, microRNAs, and small molecules, have recently been reported ( Chang et al, 2009 ; Kaji et al, 2009 ; Kim et al, 2009 ; Sommer et al, 2009 ; Woltjen et al, 2009 ; Yu et al, 2009 ; Zhou et al, 2009 ; Jia et al, 2010 ; Warren et al, 2010 ; Anokye-Danso et al, 2011 ; Rao and Malik, 2012 ; Hou et al, 2013 ), which have shown variable yields and reproducibility. Recently, Sendai viruses have been established and shown to be able to reprogram dermal fibroblasts, CD34+ hematopoietic cells and urine derived cells ( Fusaki et al, 2009 ; Ye et al, 2013 ; Afzal and Strande, 2015 ; Rossbach et al, 2016 ). As negative sense RNA viruses, Sendai viruses do not integrate into the genome of human cells and are non-pathogenic to humans ( Fusaki et al, 2009 ; Ban et al, 2011 ; Macarthur et al, 2012a ).…”
Section: Introductionmentioning
confidence: 99%
“…The urine supernatant was discarded after aspiration and the remaining pellet with particulate portion was resuspended with 2 mL of collection/storage media (1 volume Keratinocyte Serum Free (KSF) Medium, 1 volume Progenitor Cell Medium + 1 volume FBS). Samples were stored on ice for 24–48 hrs until transported back to the laboratory where the urine cell isolation and culturing continued as described by Afzal and Strande (Afzal and Strande 2015). The cells were expanded for a maximum of 5 passages when they were either directly reprogrammed or banked in liquid nitrogen for future experiments.…”
Section: Methodsmentioning
confidence: 99%